Hidden victims: the gendered data gap of violent crime - Cooper, Kerris (The British journal of criminology, 2021)
The official measure of violent crime, reported by the Office for National Statistics using the Crime Survey for England and Wales (CSEW), excludes sexual offences and neglects the self-completion survey data which more reliably captures sexual and domestic violence. In failing to include these gendered forms of violence, the official picture of who is most at risk of violence is skewed, suggesting men are at greater risk than women. This research re-estimates who is most at risk of violence, incorporating sexual and domestic violence and analysing trends in violence between 2005 and 2018 by gender. The findings challenge official statistics, revealing that women were at greater risk of violence than men in 2018.